TASK BASED LEARNING APPROACH A STRATEGIC INTERVENTION IN ENHANCING ENGLISH-SPEAKING SKILLS - JOHN KYLE B. VILBAR; GIDO, NATHANIEL G.; NESTOR CAHUTAY JR; EMERSON JOHN D. CHIN, BSIT (International Journal of Multidisciplinary Research and Studies, 2023)
Task Based Learning is available way back years ago but the utilization is not widely spread and utilized especially in the Philippine setting. This study evaluates how effective Task Based Learning in enhancing English speaking skills of the students. Study uses quasi-experimental utilizing pretest-posttest design. The data gathered were presented, interpreted and analyzed. Results showed that entries of control and experimental groups have no significant difference. The entry and exit of the control group have negative significant difference. The entry and exit of the experimental group have significant difference. And, exit of both groups have significant difference because students who are immersed in the Task Based Learning increases performance. Therefore, based on the findings, Task Based Learning Approach is effective in enhancing English speaking skills of the students.